Structural analysis of the management science methodology - Lisiński, Marek (Business, Management and Economics Engineering, 2013)
The article presents a structure of management science methodology, reduced to determination and description of its basic components. It has been covered in three levels, differing in the degree of detail description of methods. These are accordingly: the 1st level, identified with philosophy of methodology, the 2nd level corresponding to a method as well as the 3rd level, the most detailed, convergent with a technique. A structural analysis was used for identification and providing characteristics of particular components of the management science methodology.